Criação de identidade visual e material de divulgação para a instituição Clube de Mães Aliança - Poser, Rafaela (2013)
This paper describes and provides theoretical basis for the production process of a visual identity and publicity material for Clube de Mães Aliança institution. Through research presented here, relevant areas of a media production of a film are discussed, such as: demographical context, handicraft research, description about institution and methodology. The methodology adopted to create the graphic project is based on problematization, conception and specification.